2019
DOI: 10.1101/735670
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuronal activity triggers uptake of hematopoietic extracellular vesicles in vivo

Abstract: Communication with the hematopoietic system is a vital component of regulating brain function in health and disease. Traditionally, the major routes considered for this neuroimmune communication are either by individual molecules such as cytokines carried by blood, by neural transmission, or in more severe pathologies, by entry of peripheral immune cells into the brain. In addition, functional mRNA from peripheral blood can be directly transferred to neurons via extracellular vesicles (EVs) but the parameters … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Furthermore, transgenic Cre-driver as well as Cre-reporter mouse lines are already available and can be applied for EV research. Using a haematopoietic Cre-driver crossed to stopflox YFP reporter line, it was shown that Cre-containing EVs originating from peripheral immune cells enter the brain and recombine neurons in particular under inflammatory conditions and following increased neuronal activity (100,104). Careful controls such as transplantation of the hematopoietic Cre-driver bone marrow into reporter mice or injection of isolated Cre-carrying EVs were performed to provide the proof that recombination is indeed due to the transfer of EVs and not resulting from reporter leakiness.…”
Section: Tracking Evs Using Enzymatic Reportersmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, transgenic Cre-driver as well as Cre-reporter mouse lines are already available and can be applied for EV research. Using a haematopoietic Cre-driver crossed to stopflox YFP reporter line, it was shown that Cre-containing EVs originating from peripheral immune cells enter the brain and recombine neurons in particular under inflammatory conditions and following increased neuronal activity (100,104). Careful controls such as transplantation of the hematopoietic Cre-driver bone marrow into reporter mice or injection of isolated Cre-carrying EVs were performed to provide the proof that recombination is indeed due to the transfer of EVs and not resulting from reporter leakiness.…”
Section: Tracking Evs Using Enzymatic Reportersmentioning
confidence: 99%
“…EVs released by cells of the haematopoietic lineage target the brain parenchyma and were shown to transfer cargo including functional Cre reporter mRNA to neurons, which was accompanied by an altered mRNA profile in the recipient cells. This signaling occurred rarely under physiological conditions but was highly elevated in response to different inflammatory stimuli or neuronal activity (100,104). Likewise, inflammatory conditioning triggered human red blood cell (RBC)-EVs, which carry α-synuclein, to Accepted Article enter the mouse brain and target microglia where they induced a pro-inflammatory phenotype.…”
Section: Accepted Articlementioning
confidence: 99%